ChemInform Abstract: Anion Recognition by Simple Chromogenic and Chromo‐Fluorogenic Salicylidene Schiff Base or Reduced‐Schiff Base Receptors. Issue 33 (19th August 2014) - Dalapati, Sasanka; Jana, Sankar; Guchhait, Nikhil
Abstract Review: 41 refs.